Mental health pekerja Generasi Z: technostress dan burnout - Kristin Handayani; Rona Guines Purnasiwi (Jurnal Manajemen, 2025)
Lack of impulse control over excessive technology consumption causes addiction and affects mental health in this digital era. Generation Z as a massive organic workforce in the use of technology is vulnerable to mental health disorders. Previous research on the effects of excessive internet use shows that workers who are involved without control are vulnerable to technological stress. Differences in work attitudes become fatigue that intervenes in the mental health of Generation Z in the workplace. The main objective of this study is to verify whether there is an influence between technostress and burnout on the mental health of Generation Z. This study involved 55 respondents. Indicator of Mental Health Scale, indicators for measuring technostress, and indicators to measure the level of burnout for measure influence. With SPSS 31 show that the highest technostress is related to the speed of technology that is greater than the limits of individual capabilities of Gen Z. The highest burnout is due to the feeling of perception of responses in the workplace. The regression model explains 63.1% of the variance in mental health (R² = 0.631). Future implications require more in-depth research linking the work ecosystem with Millennials and Generation X.